Effect of Cycling and Washing in Fouling Level from Theaflavin Filtration on Ultrafiltration Membrane - Nyamiati, Retno Dwi; Yulianto, Mohamad Endy; Nanda, Dodi Eko; Diwiyanto, Yusron Mahendra (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Ultrafiltration membranes, characterized by their molecular weight cutoff ranging from 50 to 100 kDa, are extensively employed for the filtration of macromolecules including suspended solids, carbohydrates, proteins, and various other components. However, the prolonged usage of these membranes leads to a notable decline in their performance due to fouling. Membrane fouling entails the accumulation of filtered foulant media and the formation of deposits, adversely impacting the filtration efficiency. This study focuses on evaluating the impact of repeated filtration cycles on membrane fouling and investigates the effectiveness of membrane washing in restoring membrane performance. The ultrafiltration membrane was subjected to five consecutive repetition cycles using theaflavin as the filtration media. The observed flux exhibited a substantial decline of 87%, decreasing from an initial value of 0.0574 L/m2.hr to 0.0073 L/m2.hr. To mitigate fouling and enhance membrane performance, a thorough washing process was carried out. Following the washing procedure, the flux was found to increase to 0.034 L/m2.hr, indicating a significant improvement in the membrane's performance. These findings are further supported by the morphological analysis of the membrane using Scanning Electron Microscope (SEM) photographs, which reveal the distinct differences between the membrane's morphology before and after washing.